The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.2527/jas1980.512344x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary and Injectable Vitamin E and Selenium in Weanling Swine Antigenically Challenged with Sheep Red Blood Cells

Abstract: Two experiments were conducted to evaluate the effect of supplemental vitamin E and (or) Se, provided either in the diet or by injection, on humoral antibody production in weanling swine after an antigenic challenge with sheep red blood cells (SRBC). In the first experiment, a 2 x 2 factorial design was used, with pigs fed either 0 or .5 ppm Se and 0 or 220 IU vitamin E/kg diet. The basal diet contained a natural Se and alpha-tocopherol content of .02 ppm and 7 mg/kg, respectively. In a second 2 x 2 factorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
4
3

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 9 publications
2
35
4
3
Order By: Relevance
“…Thus, a relatively narrow range of selenium concentrations must be maintained for optimal function of the immune system. 2,3,7,12,13,16,21,25,27,29,30,32 This study and results of a field investigation failed to clarify the association between subclinical selenium toxicosis and abortion/perinatal mortality. However, data from a limited number of animals suggest that current values indicative of perinatal selenium toxicosis (Ն3 ppm) may underestimate the resistance of animals to chronic selenium toxicosis and that marked elevations in hepatic selenium concentration (Ͼ9 ppm) may be clinically relevant.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, a relatively narrow range of selenium concentrations must be maintained for optimal function of the immune system. 2,3,7,12,13,16,21,25,27,29,30,32 This study and results of a field investigation failed to clarify the association between subclinical selenium toxicosis and abortion/perinatal mortality. However, data from a limited number of animals suggest that current values indicative of perinatal selenium toxicosis (Ն3 ppm) may underestimate the resistance of animals to chronic selenium toxicosis and that marked elevations in hepatic selenium concentration (Ͼ9 ppm) may be clinically relevant.…”
Section: Discussionmentioning
confidence: 91%
“…2,14,21,32 Results from this study indicate that elevated selenium intake adversely affects several bovine leukocyte function parameters. Although outward signs of selenium toxicosis were not apparent, the ability of cultured lymphocytes to produce antibody following stimulation was significantly depressed in cows from both selenium-supplemented groups.…”
Section: Discussionmentioning
confidence: 94%
“…The influence of this intoxication on these parameters are poorly described in the literature for pigs; however, there are studies demonstrating hematotoxic and hepatotoxic actions of ZEA in rats and mice (Maaroufi et al 1996, Abbés et al 2006, Stadnik et al 2009). The evaluation of SRBC antibody titers was used extensively in the literature (Peplowski et al 1980, Bonnette et al 1990, Rotter et al 1994 to study the immune response of animals. It is known; however, that the immune response to different challenges is extremely complex.…”
Section: Discussionmentioning
confidence: 99%
“…This is important in maintaining cell membrane integrity and immune status of the animal. Low vitamin E in piglets induces a variety of lesions such as skeletal muscle degeneration, mulberry heart disease (Van Vleet, 1980) and depression of immune function (Peplowski et al, 1981 ). Ullrey (1981) also reported that vitamin E may also play a role in the immune response to infection.…”
Section: Introductionmentioning
confidence: 99%